Actinomycin Production Persists in a Strain of Streptomyces antibioticus Lacking Phenoxazinone Synthase - Jones, George H. (American Society for Microbiology, 2000)
Truncated fragments of the phenoxazinone synthase gene, phsA, were prepared by the PCR. The resulting fragments were cloned into conjugative plasmid pKC1132 and transferred to Streptomyces antibioticus by conjugation from Escherichia coli. Two of the resulting constructs were integrated into the S. antibioticus chromosome by homologous recombination, and each of the resulting strains, designated 3720/pJSE173 and 3720/pJSE174, contained a disrupted phsA gene. Strain 3720/pJSE173 grew poorly, and Southern blotting suggested that genetic changes other than the disruption of the phsA gene might have occurred during the construction of that strain. Strain 3720/pJSE174 sporulated well and grew normally on the medium used to prepare inocula for antibiotic production. Strain 3720/pJSE174 also grew as well as the wild-type strain on antibiotic production medium containing either 1 or 5.7 mM phosphate. Strain 3720/pJSE174 was shown to be devoid of phenoxazinone synthase (PHS) activity, and PHS protein was undetectable in this strain by Western blotting. Despite the absence of detectable PHS activity, strain 3720/pJSE174 produced slightly more actinomycin than did the wild-type parent strain in medium containing 1 or 5.7 mM phosphate. The observation that strain 3720/pJSE174, lacking detectable PHS protein or enzyme activity, retained the ability to produce actinomycin supports the conclusion that PHS is not required for actinomycin biosynthesis in S. antibioticus.